Ummah Imaginations in Plural Kerala: Being International in the Traditional Way - Mamdooh Abdul Fathah (Universitas Islam Negeri Mataram, 2021)
Quranic ‘Ummah’ with its political and social sensibilities in a period of authoritatively heterogenetic counter-resurgences is significant for Muslims constituting minority in Kerala, India. However, ‘Ummah’ as an euphemism for state-centered political aspirations become endemic to them only in the last century. This tendency could be linked to literal scriptural interpretations, contempt for the technocratic and mystic traditions and the idea of sacred-geographies pushed inward by reformist movements since 1920s, which disjuncts with classical hermeneutic traditions followed by Keralite Ulama by their distinctive longue-durée to mainstream Muslims lands. Recently through a revivalist campaign, the traditional Ulama refurnished their monolithic concept of Ummah by reimagining and re-appropriating those sacred imaginaries from the puritanical-Islamist claim of the pure. An embedded Ummah locality – a mixture of local products and global variants – thus piggybacked on the structural and cultural forces of globalization, allowing Ulama to prudently redraw the boundaries of national culture and its ally, local Islam. Through this paper, I try to explicate how traditional Muslim scholarship in Kerala employed Quranic Ummah in the plural society while structurally re-embedding it with the global Muslim whole. A short reflection on the interpretive paradigm of puritanical-Islamist orientations on the concept of Ummah will be given along to place various paradigms in a comparative framework.